Simultaneous voltammetric analysis of lead, copper and mercury ions by carbon paste electrode based on 1-(3-aminopropyl) imidazole modified polymer - Bayraktar, Cansu; Cankurtaran, Husnu; Senkal, Bahire Filiz (TAYLOR & FRANCIS LTD, 2018)
In this study, a carbon paste electrode modified with a novel 1-(3-aminopropyl) imidazole functionalised crosslinked chlorosulfonated poly(styrene)-divinyl benzene polymer was used for selective and sensitive determination of the trace amounts of Pb2+, Cu2+ and Hg2+ ions by square wave anodic stripping voltammetry. The effect of some parameters such as paste composition, pH, preconcentration time, reduction potential and time, type of supporting electrolyte and potential scan rate on the determination of metal ions were investigated to find the optimal conditions. The effective open-circuit accumulation of the studied metal ions was succeeded only by the modification of the carbon paste electrode with functional polymer. For 6min open-circuit preconcentration, the detection limit of Pb2+, Cu2+ and Hg2+ was found to be 5, 9 and 14 mu gL(-1), respectively at 100mVs(-1). The results confirmed that the lower concentration levels of these trace metal ions can be determined with the increase of preconcentration time and/or potential scan rate. Good detection limits and large dynamic concentration ranges were also obtained for their binary and ternary mixtures. The optimised method was successively applied to determine the concentration of Pb2+, Cu2+ ions in the tap water sample and Cu2+ ion in the waste water sample in the presence of possible interfering species (RSD<1%, recoveries 96-110% for 4min preconcentration).
Keywords: Carbon paste electrode; anodic stripping; trace metal ions; lead; copper; mercury; CHEMICALLY-MODIFIED ELECTRODES; ANODIC-STRIPPING VOLTAMMETRY; WATER SAMPLES; ONLINE PRECONCENTRATION; METAL-IONS; HG(II); CADMIUM(II); PB(II); ACID; SILVER(I); Chemistry; Environmental Sciences & Ecology